Step-by-step orthopaedics training of simulation skill of osteosynthesis by the method of Peyton - Sulyma, Vadym; Bihun, Roman (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Obtaining of surgical skills in «Ideal Conditions» with simulation training can improve the results in practice both for beginners and experienced specialists. There are various methodological approaches to the gradual mastery of a certain skill. Methodology of Peyton provides four steps: demonstration, deconstruction, comprehension, performance. Objective: to determine the effectiveness of obtaining a simulation osteosynthesis skills by orthopedic physicians during training with Peyton method. Methods: we made a four-step Peyton’s simulated practical training of osteosynthesis with stable-functional extra-bone fixators LCP on dummies with isolated fragments of a complex intra-articular fracture. Physicians (35) were divided into two groups according to their experience. The initial level of theoretical knowledge was determined by standard tests. The effectiveness of mastering a skill was assessed by the developed six-point scale. Results: the initial level of theoretical knowledge averaged 27 % for cadet physicians and 13 % for residents. When teaching practical skills, the assimilation of material among traumatologists on step I is estimated at (23.3 ± 7.2) %, step II — (29.5 ± 5.5) %, III — (42.3 ± 8.6) %, IV — (46.2 ± 5.4) %. The indices of residents almost at the first and second steps were (25.3 ± 6.7) % and (35.5 ± 9.5) %, respectively. At the end of step ІІІ (comprehension), an improvement in the assimilation of the material was observed among residents — (51.1 ± 8.1) %, and among experienced physicians — (57.7 ± 6.3) % at step IV. Conclusions: Peyton’s four-step approach showed significant advantages in teaching of practical instrumental skills of complex osteosynthesis. The most significant to assimilate the material, step III should be considered — comprehension. Despite the advantages of Peyton method in teaching of practical skills, new methods of assimilation and modification of existing ones should be done.